NMR detection in biofluid extracts at sub-μM concentrations via para-H2 induced hyperpolarization. Issue 13 (25th May 2016) - Reile, I.; Eshuis, N.; Hermkens, N. K. J.; van Weerdenburg, B. J. A.; Feiters, M. C.; Rutjes, F. P. J. T.; Tessari, M.
Abstract : A combination of solid phase extraction, para -hydrogen induced hyperpolarization and selective NMR detection allows the quantitative determination of a doping substance at sub-μM concentrations in urine. Abstract : NMR spectroscopy is one of the most powerful techniques to simultaneously obtain qualitative and quantitative information in chemical analysis. Despite its versatility, the applications of NMR in the study of biofluids are often limited by the insensitivity of the technique, further aggravated by the poor signal dispersion in the 1 H spectra. Recent advances in para -H2 induced hyperpolarization have proven to address both these limitations for specific classes of compounds. Herein, this approach is for the first time applied for quantitative determination in biofluid extracts. We demonstrate that a combination of solid phase extraction, para -hydrogen induced hyperpolarization and selective NMR detection quickly reveals a doping substance, nikethamide, at sub-μM concentrations in urine. We suggest that this method can be further optimized for the detection of different analytes in various biofluids, anticipating a wider application of hyperpolarized NMR in metabolomics and pharmacokinetics studies in the near future.